2022
DOI: 10.3390/metabo12111046
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Cottonseed Protein Concentrate Levels on Growth Performance, Health Status, Flesh Quality and Intestinal Microbiota of Grass Carp (Ctenopharyngodon idellus)

Abstract: The aim of this study was to evaluate the nutritional value of cottonseed protein concentrate (CPC) as a single dietary protein source and the optimal protein level for grass carp (Ctenopharyngodon idellus). An 8-week feeding trial was conducted by feeding juvenile grass carp (initial body weight: 4.68 ± 0.01 g) with six experimental diets containing graded levels of protein provided by CPC. The results showed that the optimal CPC level (CPC4) improved the growth performance and health status of grass carp. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 41 publications
1
2
0
Order By: Relevance
“…As a support for our finding, a study of Nile tilapia (Oreochromis niloticus) showed that less than 30% soybean meal replaced by CPC did not lead to a significant decrease in growth condition [33]. There is also a consensus among the studies mentioned above that the significantly reduced growth performance in fish fed a diet with excessively high levels of CPC may be linked to poor blood biochemistry, influenced digestibility, weakened intestinal antioxidant and immune barriers, and disrupted intestine microbiota [15,18,[31][32][33]. Therefore, we will focus on these aspects of the in-depth discussion.…”
Section: Suitable Substitution Of Fishmeal With Cpc Contributes To Th...supporting
confidence: 79%
See 1 more Smart Citation
“…As a support for our finding, a study of Nile tilapia (Oreochromis niloticus) showed that less than 30% soybean meal replaced by CPC did not lead to a significant decrease in growth condition [33]. There is also a consensus among the studies mentioned above that the significantly reduced growth performance in fish fed a diet with excessively high levels of CPC may be linked to poor blood biochemistry, influenced digestibility, weakened intestinal antioxidant and immune barriers, and disrupted intestine microbiota [15,18,[31][32][33]. Therefore, we will focus on these aspects of the in-depth discussion.…”
Section: Suitable Substitution Of Fishmeal With Cpc Contributes To Th...supporting
confidence: 79%
“…The reason why CPC can replace fishmeal at a high level could be that CPC has a higher nutritional value of protein, better palatability, and contains fewer allergenic antigens by way of low-temperature extraction, dephenolization, and desugarization [14]. For representative cyprinid fish, the studies of grass carp (Ctenopharyngodon idellus) [18,19] have also confirmed the feasibility of replacing soybean meal in feed with cottonseed protein concentrate. Our previous study also found that substituting soybean meal for CPC can not only promote the growth of common carp and feed utilization efficiency but also optimize the amino acid composition, texture characteristics, and water-holding capacity of muscle and enhance the flavor and taste of fish [20].…”
Section: Introductionmentioning
confidence: 99%
“…T-AOC, SOD, and GSH-Px are considered essential markers of antioxidant capacity, which eliminates excessive ROS in the body [30,31]. Liu et al found that the T-AOC and activity of GSH-Px in the hepatopancreas of grass carp fed with CPC significantly increased, while the content of MDA significantly decreased [7].…”
Section: Discussionmentioning
confidence: 99%
“…The preparation steps of CPC are as follows: cottonseed is physically separated by a shelling machine to obtain cottonseed, and the cottonseed embryo sheet formed after rolling is dephenolized via chemical reagents (a mixture of methanol and n-hexane solvent). The product is rapidly dried at low temperatures to produce the finished CPC [7]. This enables the removal of several anti-nutritional factors, including free gossypol, cyclopropene fatty acids, and mycotoxins, which had previously restricted the use of cottonseed meal [8].…”
Section: Introductionmentioning
confidence: 99%
“…CPC is derived from cottonseed through dephenolisation process. Recently, Liu et al 84 fed juvenile grass carp with six diets containing graded levels of protein solely provided by CPC. Texture parameters (hardness, cohesiveness, chewiness, and gumminess) of cooked meat increased initially and then decreased with increasing CPC contents in a quadratic manner.…”
Section: Strategies To Regulate Texture Characteristics In Aquaculturementioning
confidence: 99%